Exploring the Fundamental Cause of Social Crime: A Study of Sexual Violence, Mass Murder, Burglary, and Corruption - Gurung, Raj Kumar (Molung Educational Frontier, 2023)
There are effective police mechanisms administered by the governments in each country, for instance, the Central Bureau of Investigation (CBI) in India and the Central Bureau of Investigation (CBI) of Nepal Police in Nepal. The authority claims its mechanism is intact and highly alert to find convicts, but they appear to be walking out in the street freely. This indicates that the police mechanisms have been unable to control the crimes despite their high alerts. This article explores the fundamental causes of social crimes that are increasing alarmingly. The study shows that the fundamental cause of crime is the inherent weakness of a person who cannot control emotions of jealousy and anger. The uncontrolled anger of a person leads them to the stage of crime. The criminal may also have psychological disorder leading to accidental crime. Several types of social crime are prevalent, but this study discusses the causes of sexual violence, mass murder, burglary, and corruption. The study has applied the psychoanalytical approach to investigate the issue.